الأمواج السبينية في المغانط الحديدية ذات سبين - رستم, زياد (Latakia University Journal -Basic Sciences Series, 2018)
يهدف هذا العمل هو دراسة الأمواج السبينية المتشكلة في المغانط الحديدية, نتيجة إزاحة أو تغير اتجاه أحد العزوم المغناطيسية, المرتبة بشكل متوازٍ وفي اتجاه واحد التي تنتشر في الجسم الصلب بطاقة محددة تبعاً للوضعيات الاحتمالية للعزوم المغناطيسية. وهي تنطلق من نموذج هايزنبرغ الكمي للحصول على القيم الطاقية الخاصة, وذلك بإتباع طرائق كلاسيكية لوصف تلك الظاهرة المكممة. وقد تم في الخطوة الأولى تم بناء التابع الموجي المناسب ثم الحصول على الهاميلتوني و اللاغرانجيان ومعادلة الحركة, و بإيجاد الحلول المناسبة لتلك المعادلة نحصل على قوانين التشتت و القيم الطاقية وتبين أنه يمكن إسقاط هذه الطريقة لوصف حركة الجسيمات الحرة (إلكترون) في الجسم الصلب التي تملك صفات موجية اذ إنّه يمكن بإجراء تقريبي مقبول الحصول على معادلة شرودنغر. The purpose of this article is to study the spin waves formed in the Ferromagnetics, as a result of displacement or change in the magnetic moment’s direction, ordered in a parallel and in one direction, these waves propagates in solid matter with an energy determined by the probability locations of the magnetic moments. This study is based on the Heisenberg Quantum Model, to obtain energy values, using classical methods to describe that Quantum phenomenon. We established in the first step the suitable wave function, and then we obtained the Hamiltonian, the Lagrangeian and the equation of motion. By finding the suitable solution to that equation, we could find the Scattering laws and the energy values. Also it was found that we can this method to describe the movement of free particles (the electrons) in soled matter, which has a wave properties, i.e. by making an acceptable approximation, we can deduce the Schrodinger equation.